Medications for attention‐deficit/hyperactivity disorder in Japan: A retrospective cohort study of label compliance. Issue 3 (28th June 2021) - Fife, Daniel; Voss, Erica A.; Hardin, Jill; Rofael, Hany; Solomon, Ira D.; Ryan, Patrick B.; Stang, Paul
Abstract: Aim: To assess label compliance in prescription of medications approved for treatment of attention‐deficit/hyperactivity disorder (ADHD) in Japan at the time of this study: methylphenidate (MPH), atomoxetine, and guanfacine. Methods: Retrospective descriptive study was conducted in prevalent‐user cohorts from the Japan Medical Data Center database. Patients who were prescribed a study drug between January 1, 2013 and September 30, 2018 and were in the database for ≥30 days were included. A prescription was considered compliant if all 4 criteria were satisfied: appropriate age, daily dose not exceeding the approved maximum, no contraindicated concurrent medications, and no contraindicated conditions. Results: Among 17 418 patients who were prescribed a study drug during 2013‐2018, 73% were male and 53% were children (aged <18 years). Fewer than 2% of prescriptions were for patients outside the approved age, 10%‐13% of patients in the atomoxetine and MPH cohorts received ≥1 prescription exceeding maximum approved dose, no patients were co‐prescribed a contraindicated medication, and 16%–18% of patients in the MPH cohorts had ≥1 contraindicated condition. During their first 500 days of use, for approximately 73%‐86% of patients, all prescriptions were compliant with all label requirements. Conclusions: Among patients exposed to ADHD medications in Japan during 2013‐2018, nearly all prescriptions for these medications were label‐compliant for age. For >85% of patients, all prescriptions were label‐compliant for dose, and for approximately 80%, all prescriptions were label‐compliant for contraindicated conditions. We did not find evidence of widespread abuse or noncompliant use of prescribed ADHD medications. Abstract : To assess label compliance in prescription of medications approved for the treatment of ADHD in Japan at the time of this study (2013‐2018), a retrospective descriptive cohort study was conducted in patients from the JMDC database who were prescribed a study drug (methylphenidate, atomoxetine, or guanfacine) and were in the database for at least 30 days. Among 17 418 patients eligible for the study, nearly all prescriptions were label‐compliant for age; for more than 85% of patients, all prescriptions were label‐compliant for dose, and for approximately 80%, all prescriptions were label‐compliant for contraindicated conditions. We did not find evidence of widespread abuse or noncompliant use of prescribed ADHD medications.